FROM APOLLO TO BUDDHA: TRANSFORMATION OF CLASSICAL IDEALS IN EARLY INDIAN SCULPTURE - Saxena, Chandni (ShodhKosh: Journal of Visual and Performing Arts, 2026)
‘Greek Art did not simply travel East; it was transformed in the process’. -John Boardman ‘The Diffusion of Classical Art in Antiquity’ With the invasion of Alexander in 326 BCE, India witnessed an entirely novel set of culture, traditions, art and artistic expressions. He entered into the country through the passes of Hindukush into the region historically known as Gandhar and Punjab (present day Pakistan and Northwest India). Through his wars and conquests, Alexander formed an empire whose western boundary constituted regions west of Indus which was already a part of his Achaemenid conquests. On eastern front, he reached till Beas (Hyphasis) river and planned to invade the powerful Nanda Empire of Magadh. But he had to turned back due to his troops’ mutiny. Moving towards south, he sailed down the Indus River to the Arabian Sea and left a garrison in Sindh and Punjab. Despite his desire to do so, he did not penetrate into the Gangetic plains or Central India. Even after his death, Greek presence continued in India till 1st century CE, with the cultural influences lasting much longer.